2007
DOI: 10.1128/iai.00031-07
|View full text |Cite
|
Sign up to set email alerts
|

Pneumolysin Causes Neuronal Cell Death through Mitochondrial Damage

Abstract: Bacterial toxins such as pneumolysin are key mediators of cytotoxicity in infections. Pneumolysin is a pore-forming toxin released by Streptococcus pneumoniae, the major cause of bacterial meningitis. We found that pneumolysin is the pneumococcal factor that accounts for the cell death pathways induced by live bacteria in primary neurons. The pore-forming activity of pneumolysin is essential for the induction of mitochondrial damage and apoptosis. Pneumolysin colocalized with mitochondrial membranes, altered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 42 publications
4
92
1
2
Order By: Relevance
“…A pneumococcal exotoxin (ExoY) has been reported for its potential to cause endothelial Tau hyperphosphorylation (Ochoa et al, 2012). While reports related to direct role of ExoY in the onset of AD are lacking, there are reports regarding bacterial and viral involvement in the pathogenesis of neurodegeneration (Braun et al, 2007;Chiara et al, 2012;Nicolson & Haier, 2009). Pseudomonas aeruginosa is known to be an opportunistic human pathogen that causes microbial infection in immunocompromised condition, especially in old age (Gellatly & Hancock, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pneumococcal exotoxin (ExoY) has been reported for its potential to cause endothelial Tau hyperphosphorylation (Ochoa et al, 2012). While reports related to direct role of ExoY in the onset of AD are lacking, there are reports regarding bacterial and viral involvement in the pathogenesis of neurodegeneration (Braun et al, 2007;Chiara et al, 2012;Nicolson & Haier, 2009). Pseudomonas aeruginosa is known to be an opportunistic human pathogen that causes microbial infection in immunocompromised condition, especially in old age (Gellatly & Hancock, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The study indicates therapeutic potential of Himalayan lichen C. olivetorum against neurodegenerative diseases, encourages its commercial exploitation through mass culture and suggests further research on purification of bioactive components responsible for the observed biological activities. Furthermore, it has also been reported that herpes simplex virus (HSV-1) has considerable involvement in neuronal damage (Braun et al, 2007;Chiara et al, 2012), hence antiviral potential of bioactive components should also be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…In macrophages there exists a low-level of apoptosis following exposure to non-opsonised largely extracellular bacteria [54]. Still, the production hydrogen peroxide by the pneumococcus induces cell death in neurons, microglia and brain microvascular endothelial cells [21,[58][59][60] also studied a variety of other pneumococcal factors in the induction of microglial apoptosis and found no role for choline binding protein A, autolysin, surface IgA protease, zinc metalloprotease, pneumococcal surface antigen A or the comA gene involved in DNA transformation [60]. In monocyte-derived macrophages autolysin, neuraminidase or hyaluronidase did not influence apoptosis induction [54].…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%
“…Pneumolysin activates the innate immune system through Toll-like receptor 4 (TLR4) [53] and described as induced neuronal apoptosis without activating caspase-1, -3, or -8. However, the pneumolysin functions as a mitochondrial toxin is considered as a determinant of caspase-independent apoptosis [21].…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%
See 1 more Smart Citation